Efektivitas Aplikasi Mobile Terintegrasi Internet of Things dalam Edukasi dan Pemantauan Mandiri Pasien Ginjal Kronis - Madyo Maryoto; Sugeng Riyadi; Mardiyono Mardiyono (JURNAL KEPERAWATAN MERSI, 2026)
Background: Chronic kidney disease (CKD) is a global health problem with a prevalence of approximately 10–15% of the adult population and often goes undetected until advanced stages. Management of this disease requires long-term monitoring and active patient involvement in self-management. Advances in digital health technologies such as mobile applications and the Internet of Things (IoT) offer innovative approaches to improve health education and real-time patient monitoring. Objective: To analyze the effectiveness of using an IoT-integrated mobile application in improving clinical outcomes and self-management adherence in CKD patients. Methods: The study used a quasi-experimental design with a two-group approach (intervention and control). A sample of 240 patients with CKD stages 1–5 was selected using a purposive sampling technique. The intervention group used a mobile application integrated with IoT devices such as blood pressure monitors (smart blood pressure monitor) and digital scales (smart body weight scale), while the control group received conventional care. Data analysis used independent t-tests and chi-square tests with a significance level of p<0.05. Results: The results showed that the intervention group experienced significant improvements in clinical parameters compared to the control group. Therapy adherence increased from 64% to 88% in the intervention group (p<0.001). Furthermore, patients quality of life also improved significantly. Conclusion: The use of an IoT-integrated mobile application has proven effective in improving self-monitoring, therapy adherence, and clinical parameters in CKD patients. Integrating digital technology into nursing practice can be an innovative strategy to improve the quality of care for patients with chronic diseases.